Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1210/endo.142.8.8295
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Positively Regulates Matrix Metalloproteinase Expression in Human Lower Uterine Segment Fibroblasts Using a Tyrosine Kinase Signaling Pathway

Abstract: Despite the importance of relaxin to normal parturition in various species and its potential as an etiological agent in preterm delivery in women, knowledge regarding the mechanisms by which relaxin alters cervical connective tissue is extremely limited. An established in vitro model for human pregnancy cervix, human lower uterine segment fibroblasts, was used to determine the effects of relaxin as well as those of progesterone on the expression of matrix metalloproteinases and tissue inhibitor of metalloprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 45 publications
6
51
0
Order By: Relevance
“…** Western Blot Analyses. Western blot analyses employing specific, well characterized primary antibodies and semiquantitative methods described previously (29,30) were used to determine expression of the steroid hormone receptors, MMPs, and TIMP-1. Mouse monoclonal antibodies to human procollagenase (proMMP-1) (Ab-1), human prostromelysin (proMMP-3) (Ab-1), and human TIMP-1 (Ab-1), human estrogen receptor ␣ (GR17), human estrogen receptor ␤ (GR39), pure proMMP-1, proMMP-3, and TIMP-1 proteins and peroxidase-conjugated goat anti-mouse IgG and IgM were from Calbiochem͞Oncogene Research Products.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…** Western Blot Analyses. Western blot analyses employing specific, well characterized primary antibodies and semiquantitative methods described previously (29,30) were used to determine expression of the steroid hormone receptors, MMPs, and TIMP-1. Mouse monoclonal antibodies to human procollagenase (proMMP-1) (Ab-1), human prostromelysin (proMMP-3) (Ab-1), and human TIMP-1 (Ab-1), human estrogen receptor ␣ (GR17), human estrogen receptor ␤ (GR39), pure proMMP-1, proMMP-3, and TIMP-1 proteins and peroxidase-conjugated goat anti-mouse IgG and IgM were from Calbiochem͞Oncogene Research Products.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the blots were washed three times with Tris-buffered saline Tween 20 over a 30-min period and developed by the enhanced chemiluminescence method. Intensities of the signals obtained on developed films were determined with a computing densitometer (model 300B, Molecular Dynamics) by using the volume-integration method with appropriate corrections for background absorption, as we have described previously (29,30). Samples from all monkeys were run on the same blot.…”
Section: Methodsmentioning
confidence: 99%
“…1. One possibility to be discussed in detail here is based on the confluence of several observations: 1) the crucial role for RLX, the endothelial ET B receptor, and NO in pregnancy-mediated renal vasodilation as described above, 2) the ability of RLX to upregulate matrix metalloproteinase activity (MMP) activity (at least in fibroblasts; 82,105,108), and 3) the potential for vascular MMPs, such as MMP-2, to process big ET at the Gly-Leu bond to yield ET , the latter capable of activating ET receptors (31,32). Thus RLX may upregulate MMP-2 activity in the renal vasculature during pregnancy, thereby leading to renal vasodilation, hyperfiltration, and reduced myogenic reactivity of small renal arteries in an ET-and NO-dependent fashion.…”
Section: And Citations Therein)mentioning
confidence: 99%
“…This would also explain the fast widening action of locally applied RLX on the marmoset cervix obtained in our study, while RLX has been shown to stimulate a number of intracellular pathways, including those involved with NO synthase II (Samuel et al 2007a(Samuel et al , 2007b. Therefore, RLX seems to act differently on cervical ripening: a mediator of collagen turnover by stimulating the breakdown of collagen through MMP stimulation (Palejwala et al 2001 In all hormonal treated groups, a decline (not significant) in cervical collagen content was detected by histological and biochemical means. This reduction of collagen was due to different mechanisms, involving an increased local MMP release, number of eosinophil cells and RLX responsibility of the cervical tissue by increasing RXFP1 expression.…”
Section: Discussionmentioning
confidence: 85%